(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Withthe advent of liberalization policy and RBI’s easy norms several private andforeign banks have entered in Indian banking sector which has given birth tocut throat competition amongst banks for acquiring large customer base andmarket share. Banks have to deal with many customers and render various typesof services to its customers and if the customers are not satisfied with theservices provided by the banks then they will defect which will impact economyas a whole since banking system plays an important role in the economy of acountry, also it is very costly and difficult to recover a dissatisfiedcustomer. Since the competition has grown manifold in the recent times it hasbecome a herculean task for organizations to build loyalty, the reason being thatthe customer of today is spoilt for choice. It has become imperative for bothpublic and private sector banks to perform to the best of their abilities toretain their customers by catering to their explicit as well as implicit needs.Many a times it happens that the banks fail to satisfy their customer which cancause huge losses for banks and there the need of this study arises. Thepurpose of this study is to compare the public sector banks and private sectorbanks in terms of customer satisfaction and tostudy the various variables of service quality using servqual model. The workhas been carried out with the objective of understanding the reasons ofcustomer dissatisfaction and what are the opportunity areas wherein these banksneed to focus and strengthen their Customer Relationship Management practices.The research work uses both the sources of information, i.e. Primary andSecondary sources, and thereafter SERVQUAL model has been used to identify thediscrepancy in the service delivery system. Finally the study concludes bygiving some recommendations to improve in the area where these banks do notmeet the expectation of their customers.